2017
DOI: 10.1016/j.enconman.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid photovoltaic-thermal solar systems for combined heating, cooling and power provision in the urban environment

Abstract: Solar energy can play a leading role in reducing the current reliance on fossil fuels and in increasing renewable energy integration in the built environment. Hybrid photovoltaic-thermal (PV-T) systems can reach overall efficiencies in excess of 70%, with electrical fficiencies in the range of 15-20% and thermal efficiencies of 50% or higher. In most applications, the electrical output of a hybrid PV-T system is the priority, hence the contacting fluid is used to cool the PV cells to maximise their electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(70 citation statements)
references
References 18 publications
0
69
0
1
Order By: Relevance
“…Depending on the necessary technological requirements worked out three basic modes of HSGM working [8]: ensuring the most efficient power generation, ensuring maximum efficiency of thermal energy and maximizing the overall efficiency. In [9] developed designs that for maximize the electric power ensure the heat extraction from SC front surface to the environment and from the rear surface to the coolant circuit. The main feature of the module design that meets this working regime is the absence of air layer between the solar cells and translucent coating.…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…Depending on the necessary technological requirements worked out three basic modes of HSGM working [8]: ensuring the most efficient power generation, ensuring maximum efficiency of thermal energy and maximizing the overall efficiency. In [9] developed designs that for maximize the electric power ensure the heat extraction from SC front surface to the environment and from the rear surface to the coolant circuit. The main feature of the module design that meets this working regime is the absence of air layer between the solar cells and translucent coating.…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…and If a subsystem has n components, then the component availability A i (t) can be calculated by (6) as follows:…”
Section: Markov Modelmentioning
confidence: 99%
“…The design process of a large-scale PV plant can be performed by considering the system cost. In reference [6], it was suggested that PV/T systems can supply a major portion of domestic heating and cooling demands | 119 Some researchers have developed a model for PV module electrical efficiency evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of solar energy can be harnessed from the entire surface of the earth is 1.22x10 14 tons coal equivalent or 0.814x10 14 tons of oil equivalent in one year. That is to say, the amount of incoming solar energy on the earth surface in one year is fifty times the known reserves of coal and 800 times the known oil reserves [8]. Hence, if solar energy can be harnessed and used in a proper way, it has the capacity to fulfil multiple times the energy demands of the world population.…”
Section: Introductionmentioning
confidence: 99%